Life Cycle and Genetic Identification of Argas persicus Infesting Domestic Fowl in Khyber Pakhtunkhwa, Pakistan - Zahid, Hafsa; Muñoz-Leal, Sebastián; Khan, Muhammad Qayash; Alouffi, Abdulaziz S.; Labruna, Marcelo B.; Ali, Abid (Frontiers in Veterinary Science, 2021)
Ticks transmit numerous pathogens to animals including humans; therefore, they are parasites of health concern. Soft ticks infesting domestic fowl in Pakistan are carriers of viruses and bacteria and cause unestimated economic losses in the poultry sector. The current study was intended to identify soft ticks infesting domestic fowl and understand their spatio-temporal distribution along one year. A sum of 7,219 soft ticks were collected from 608 domestic fowl in 58 infested shelters; 938 (12.9%) ticks were found on the host and 6,281 (87%) in the shelters. The collected ticks comprised 3,503 (48.52%) adults including 1,547 (21.42%) males and 1,956 (27.09%) females, 3,238 (44.85%) nymphs and 478 (6.62%) larvae. The most prevalent life stages were adults, followed by nymphs and larvae. Overall tick prevalence considering all visited shelters was 38.66% (58/150). The highest tick prevalence was found in district Lakki Marwat (50.03%) followed by Peshawar (31.08%), and Chitral (18.88%) districts. All ticks were morpho-taxonomically identified as Argas persicus. To determine their life cycle, adult A. persicus were reared in the laboratory infesting domestic fowl (Gallus gallus domesticus). The life cycle was completed in 113-132 days (egg to egg) with a mean temperature of 33±3℃ and relative humidity of 65±5%. Individual ticks were used for DNA extraction and subjected to polymerase chain reaction (PCR) using specific primers for the amplification of a partial fragment of mitochondrial cytochrome oxidase subunit I (cox1) and 16S ribosomal RNA (16S rRNA) genes. Obtained amplicons were compared using BLAST to scan for homologous sequences. Phylogenetic trees showed A. persicus from Pakistan clustering with conspecific sequences reported from Australia, Chile, China, Kenya, and the United States. This is the first study aiming to reproduce the life cycle of A. persicus and genetically identify this tick in the region. Further studies are encouraged to investigate the pathogens associated with this soft tick species in Pakistan.